Integrating Technology and Culture: Smartphone Validation of a Food Frequency Questionnaire for Nutrient Intake Estimates in the Adult Population of Trinidad and Tobago - Lesley Ann Foster-Nicholas; Patricia Dyett; Celine Heskey; David Shavlik; Gina Siapco (Current Developments in Nutrition)
Background: Trinidad and Tobago is home to a multiethnic population, each with distinct dietary traditions. Given this diversity, it is essential to validate a food frequency questionnaire (FFQ) that captures the local food items that contribute to the nation’s unique dietary culture. Objectives: This study aims to assess the reproducibility and validity of a semiquantitative FFQ to estimate nutrient intake in the adult population of Trinidad and Tobago. Methods: A 139-item semiquantitative electronic food frequency questionnaire (e-FFQ), developed using Google Forms, captured culture-specific foods commonly consumed in Trinidad and Tobago. The self-administered e-FFQ was distributed to 91 participants aged 18 and older, with 2 administrations 3 mo apart. The first administration of the e-FFQ was validated against the weighted mean of 4 food records with digital images as the reference method. Data were analyzed using SPSS Version 26 to assess validity and reproducibility through paired t-tests, correlations, and cross-classification. Results: Participants had a mean age of 38 ± 9.6 y, with 22% male and 78% female. Correlations between the e-FFQ and food records ranged from moderate (r = 0.59 for vitamin C) to high (r = 0.83 for carbohydrates). Cross-classification agreements varied from 69% for cholesterol to 89% for fiber and vitamin A. Energy-adjusted correlations averaged r = 0.37, ranging from r = 0.22 for polyunsaturated fatty acids to r = 0.67 for cholesterol. Cross-classification indicated that 61% of e-FFQ estimates were correctly classified within ±1 quintile. Conclusions: The culture-specific e-FFQ demonstrates strong reproducibility and validity, making it a valuable tool for assessing nutrient intake in Trinidad and Tobago’s adult population.